An Investigation of Pakistan’s Manufacturing Sector Corporate Investment Under Financial Liberalization - Salman Ali Qureshi,Syed Muhammad Amir Shah,Syed Hassan Raza (JSSH, 2023)
Previous studies at macro level resultantly favor the financial liberalization and growth of a country. On the other side the studies conducted at the micro level show mixed results and there is a dearth of literature for accepting/rejecting the notion of financial liberalization at the micro level. The present study examines the impact of Financial Sector Reforms on the Investment of Manufacturing Sector listed at Pakistan Stock Exchange.